Enhancing Student Achievement Through Tailored Mathematics Instruction - Noviyanti, Putu Ledyari; I Made Dharma Atmaja; Ni Made Wersi Murtini (Universitas Pendidikan Ganesha, 2024)
The transition from online learning to limited face-to-face learning requires innovation in learning to increase students' motivation and learning outcomes. This study aims to develop differentiated mathematics learning to improve student learning outcomes and determine the quality of differentiated mathematics learning. This study is a development study using the ADDIE model. The data analysis technique used in this study is for the analysis stage using diagnostic assessment, while at the implementation stage using product validity data analysis by calculating the average score, data analysis to measure product practicality by calculating the average score and data analysis to measure the effectiveness of learning. The results showed that tailored mathematics instruction significantly improved students' conceptual understanding and problem-solving skills compared to traditional instruction methods. Students who received tailored instruction tended to be more active participants in learning, had higher motivation, and showed significant improvements in final test results. This suggests that a tailored instruction approach can be an effective strategy in accommodating the diversity of student abilities, helping achieve more optimal learning outcomes. The implications of this study provide a basis for education policy to further support teacher training in the application of differentiation in instruction, especially in subjects considered difficult, such as mathematics.